A simple procedure for the evaluation of treatment effects on duration variables - Jaap H. Abbring; Gerard J. van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2003)
Often, a treatment and the outcome of interest are characterized by the moment they occur, and these moments are realizations of stochastic processes with dependent unobserved determinants. We develop a simple and intuitive method for inference on the treatment effect. The method can be implemented as a graphical procedure or as a straightforward parameter test in an auxiliary univariate single-spell duration model. The method exploits information on the timing of the treatment relative to the outcome that is discarded in binary treatment analyses.
Keywords: C14; C31; C41; 330; Duration analysis; hazard rate; selectivity bias; treatment effect; unobserved heterogeneity